2014
DOI: 10.5194/acp-14-641-2014
|View full text |Cite
|
Sign up to set email alerts
|

Observation and a numerical study of gravity waves during tropical cyclone Ivan (2008)

Abstract: Abstract. Gravity waves (GWs) with horizontal wavelengths of 32-2000 km are investigated during tropical cyclone (TC) Ivan (2008) in the southwest Indian Ocean in the upper troposphere (UT) and the lower stratosphere (LS) using observational data sets, radiosonde and GPS radio occultation data, ECMWF analyses and simulations of the French numerical model Meso-NH with vertical resolution < 150 m near the surface and 500 m in the UT/LS. Observations reveal dominant low-frequency GWs with short vertical waveleng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 97 publications
3
20
0
Order By: Relevance
“…The spectral range of stratospheric GWs observed or modelled in association with TCs is extremely broad and spans multiple orders of magnitude both in terms of vertical wavelengths (from as short as 0.7 km (e.g, Chane Ming et al . ) to as long as 10 km or more [e.g. Wu and Zhang, ; Hecht et al .…”
Section: Introductionmentioning
confidence: 99%
“…The spectral range of stratospheric GWs observed or modelled in association with TCs is extremely broad and spans multiple orders of magnitude both in terms of vertical wavelengths (from as short as 0.7 km (e.g, Chane Ming et al . ) to as long as 10 km or more [e.g. Wu and Zhang, ; Hecht et al .…”
Section: Introductionmentioning
confidence: 99%
“…TC‐induced gravity waves (GWs) have been widely studied with model simulations, satellite, and ground‐based observations, as well as reanalysis data (Chen et al, ; Chane Ming et al, , ; Kuester et al, ; Kim et al, ; Miller et al, ; Nolan & Zhang, ; Wu et al, ; Yue et al, ). Typical characteristics, namely, the vertical and horizontal wavelength, period, and propagation direction have been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral analysis of the fluctuations of temperature, zonal, and meridional wind during Aila revealed that the vertical wavelengths in the range 2.5–3.2 km, corresponding to wave number of 2 to 3 cycles/km, of GW dominate in LS. Several previous studies have revealed that vertical wavelengths in the range of 0.7–3 km are dominant during tropical cyclones Hudah, Ivan, Dina, and Faxai in the LS (Chane Ming et al, ; Chane‐Ming et al, ; Chane‐Ming et al, ). Also, a previous study of GW in LS over Bay of Bengal during TCs using Welch method agrees to the present findings (Rakshit et al, ).…”
Section: Discussionmentioning
confidence: 98%